Evidence of a Genetically Distinct Population of Striped Bass within the Saint John River, New Brunswick, Canada. (21st November 2018) - Leblanc, Nathalie M.; Andrews, Samuel N.; Avery, Trevor S.; Puncher, Gregory N.; Gahagan, Benjamin I.; Whiteley, Andrew R.; Curry, R. Allen; Pavey, Scott A.
Abstract: Sound management of a species requires, among other things, careful consideration of their distribution and genetic structure throughout their range. Historically, there were three spawning populations of Striped Bass Morone saxatilis occurring within the Bay of Fundy, Canada (Shubenacadie River, Annapolis River, and Saint John River), but today the only known spawning population is found in the Shubenacadie River, Nova Scotia. The last spawning event recorded (albeit unsuccessful) in the Saint John River was in 1975 shortly after the completion of the Mactaquac Dam in 1968. Adult Striped Bass from other rivers frequent the Saint John River during much of the year, making the presence of adults uninformative about the status of spawning. In the absence of direct indicators of spawning, such as eggs and larvae, genomic tools can provide insight into the genetic origin of the juvenile Striped Bass in the Saint John River. Tissue samples were taken from Striped Bass (ages 1–3; 12.2–35.0 cm TL) captured in the Saint John River and compared with samples from the Shubenacadie River, Hudson River, and Chesapeake Bay. A double‐digest RAD‐seq technique was used to identify 4, 700 single nucleotide polymorphisms, and population structure was assessed using population differentiation statistics ( F ST ) and genetic clustering algorithms. The F ST analysis found significant differences among all sample sites, albeit weak differences between Hudson River and Chesapeake Bay samples, and a global F ST of 0.101. Genetic clustering analyses and discriminant analysis of principle components both grouped samples into three clusters: the Shubenacadie River, the U.S. populations, and the Saint John River juveniles. Based on these findings and the current understanding of Striped Bass juvenile dispersal, there is strong evidence of a genetically distinct population of Striped Bass within the Saint John River.